A multi-stakeholder portfolio optimization framework applied to stormwater best management practice (BMP) selection. (November 2017) - Di Matteo, Michael; Dandy, Graeme C.; Maier, Holger R.
Abstract: In this paper, an optimization framework for complex environmental management problems involving multiple stakeholders is developed and illustrated. In the framework, problems are represented as a series of smaller, interconnected optimization problems, reflecting individual stakeholders' interests. The framework uses interactive visual analytics to explore and analyse optimization results, and the concept of Best Alternatives to a Negotiated Agreement (BATNAs) and an approach to reframe visualizations to encourage stakeholder negotiation. To demonstrate the utility of the framework, it is applied to a realistic case study involving multiple stakeholder groups funding different stormwater best management practices (BMPs) for a catchment management plan for a region of a large city in Australia. The problem features a total of sixteen objectives for four stakeholders. The results indicate that the proposed framework enables the identification of solutions that provide optimal trade-offs between many objectives and provides an effective and efficient means of assisting stakeholders with identifying acceptable solutions. Highlights: An optimization framework handling multiple problem formulations is proposed. Each problem formulation represents one stakeholder's values and interests. Solutions to multiple problems are visualised, then jointly explored and analysed. The framework is applied to a catchment management portfolio optimization problem. Equitable compromise solutions to the sixteen-objective problem are identified.